The inflation uncertainty-inflation relationship: time variation across Latin America and the G7 - Alvarado, Mauricio (2025)
This paper examines the evolution of the inflation uncertainty-inflation relationship in seven Latin American countries and the G7 from Q1 1948 to Q4 2023, using the time-varying parameter stochastic volatility in mean (TVP-SVM) model of Chan (2017) and its extension incorporating time-varying mixture innovations (TVP-SVM-TVMI) from Hou (2020). The key findings are as follows: (i) the TVP-SVM model is preferred in 8 out of 14 countries; (ii) inflation uncertainty has been higher in Latin America than in the G7, particularly during the 1980s "lost decade"; (iii) log-inflation uncertainty is more persistent in Latin America; (iv) there is no evidence supporting the hypothesis of Friedman (1977) in any of the countries analyzed; (v) the Cukierman-Meltzer hypothesis (1986) holds, as the uncertainty-inflation relationship is positive and time-varying in all countries; (vi) this relationship is stronger and statistically significantduring periods of high inflation uncertainty; and (vii) there is evidence of more structural breaks in this relationship in Latin America than in the G7.